P.146 Exploring the Canadian management of aSAH and delayed cerebral ischemia. (June 2022) - Eagles, ME; MacLean, MA; Kameda-Smith, M; Duda, T; Almojuela, A; Bokhari, R; Elkaim, LM; Iorio-Morin, C; Persad, AR; Rizzuto, M; Lownie, SP; Christie, SD; et al.
Abstract : Background: Delayed Cerebral Ischemia (DCI) is a complication of aneurysmal subarachnoid hemorrhage (aSAH) and is associated with significant morbidity and mortality. A paucity of high-quality evidence is available to guide the management of DCI. As such, our objective was to evaluate practice patterns of Canadian physicians regarding the management of aSAH and DCI. Methods: The Canadian Neurosurgery Research Collaborative (CNRC) performed a cross-sectional survey of Canadian neurosurgeons, intensivists, and neurologists who manage aSAH. The survey was distributed to members of the Canadian Neurosurgical and Neurocritical Care Societies, respectively. Responses were analyzed using quantitative and qualitative methods. Results: The response rate was 129/340 (38%). Agreement among respondents included the need for intensive care unit admission, use of clinical and radiographic monitoring, and prophylaxis for prevention of DCI. Indications for starting hyperdynamic therapy varied. There was discrepancy in the proportion of patients felt to require intravenous milrinone, intra-arterial vasodilators, or physical angioplasty for treatment of DCI. Most respondents reported their facility does not utilize a standardized definition for DCI. Conclusions: DCI is an important clinical entity for which no consensus exists in management among Canadian practitioners. The CNRC calls for the development of national standards in the diagnosis and management of DCI.